Investigation of green material classification for green building in Libyan construction Industry - Rashd, Raja Banour (2016)
The global transition toward green building has encouraged nations to provide a proper fertile ground of legislation and standards that organize the transition to the green concept. A green materials classification is considered as one of the related issues of green building within the Libyan construction industry. That does not have a guide of classifying the green materials. This study aimed to identify the proper classifications of green building materials, as well as detennining the main challenges of classifying the green materials in Libya. This study methodology relies on both approaches, quantitative and qualitative, primary data has been collected through a survey instrument, while the secondary data has been collected through an interview instrument. The survey instrument has used to collect the primary data, while the interview instrument has conducted with three experts in the field of green building construction. A total of 223 respondents have responded to examine the study hypotheses. The descriptive results have ranked the green materials classifications as follows; recycled base, reused base, and renewable base respectively. The correlation and regression results revealed high prediction from the recycled materials base to the green materials classification, following by the reuse base of classifications, while a significantly negative association has found between the renewable and green materials classifications. Besides that, according to the interview results, five challenges have identified in common for classifying the green materials in Libyan construction industry. Facilitating appropriate solutions to meet these challenges is the responsibility of the government and practitioners in practice. This study has ended with three recommendations, which contribute to overcome the current challenges in classifying the green materials in Libya